COMPARATIVE CHARACTERISTICS OF TERMS “INNOVATION POTENTIAL” AND “INNOVATION ENSURING” IN THE CONTEXT OF SUSTAINABLE ENTERPRISE DEVELOPMENT (INNOVATIVE ECONOMY, 2025)
Komandrovska V.Ye. COMPARATIVE CHARACTERISTICS OF TERMS “INNOVATION POTENTIAL” AND “INNOVATION ENSURING” IN THE CONTEXT OF SUSTAINABLE ENTERPRISE DEVELOPMENTPurpose. The aim of the article is to provide the theoretical and methodological substantiation of the essence of the concept of “innovation support”, its differences from the term “innovation potential” and determining the nature of their interaction in the context of sustainable enterprise development.Methodology of research. Methods of systematic and comparative analysis were used in the research process to study the essential characteristics of innovation potential and innovation ensuring; structural-functional analysis to determine relationships between their elements; methods of synthesis and generalization to form a methodological approach to analysing their interaction. The theoretical and methodological basis of the research was founded on fundamental principles of innovation management, sustainable development theory, and systems approach.Findings. A comparative analysis of the concepts “innovation potential” and “innovation ensuring”  was conducted, revealing their essential characteristics and differences. A methodological approach to analysing their relationships was developed, taking into account structural, functional, and dynamic aspects of interaction. The mechanisms of synergetic effect formation from the interaction of the studied elements in the context of ensuring sustainable enterprise development were substantiated.Originality. The theoretical and methodological approach to analysing the relationship between innovation potential and innovation ensuring was improved, which, unlike existing approaches, takes into account their systemic interaction and mutual influence in the context of sustainable enterprise development. The conceptual foundations for forming the mechanism of their effective interaction, considering the synergetic effect, were developed.Practical value. The developed methodological provisions can be used in forming the innovation development management system of the enterprise, developing innovation strategies, and mechanisms for their implementation. The proposed approach will contribute to increasing the efficiency of innovation activities and ensuring sustainable development of the enterprise.Key words: innovation potential, innovation ensuring, sustainable development of enterprise, synergetic effect, systems approach, innovation development.
Keywords: innovation potential; innovation ensuring; sustainable development of enterprise; synergetic effect; systems approach; innovation development.